The Starch-Debranching Enzymes Isoamylase and Pullulanase Are Both Involved in Amylopectin Biosynthesis in Rice Endosperm - Kubo, Akiko (American Society of Plant Physiologists, 1999)
The activities of the two types of starch debranching enzymes, isoamylase and pullulanase, were greatly reduced in endosperms of allelic sugary-1 mutants of rice (Oryza sativa), with the decrease more pronounced for isoamylase than for pullulanase. However, the decrease in isoamylase activity was not related to the magnitude of the sugary phenotype (the proportion of the phytoglycogen region of the endosperm), as observed with pullulanase. In the moderately mutated line EM-5, the pullulanase activity was markedly lower in the phytoglycogen region than in the starch region, and isoamylase activity was extremely low or completely lost in the whole endosperm tissue. These results suggest that both debranching enzymes are involved in amylopectin biosynthesis in rice endosperm. We presume that isoamylase plays a predominant role in amylopectin synthesis, but pullulanase is also essential or can compensate for the role of isoamylase in the construction of the amylopectin multiple-cluster structure. It is highly possible that isoamylase was modified in some sugary-1 mutants such as EM-273 and EM-5, since it was present in significant and trace amounts, respectively, in these mutants but was apparently inactive. The results show that the Sugary-1 gene encodes the isoamylase gene of the rice genome.